DETERMINAN KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PDAM TIRTA KEUMUENENG LANGSA - Dewi Puspita Sari (Jurnal Mahasiswa Akuntansi Samudra, 2024)
This research aims to determine the effect of the use of information technology, human resource capacity and internal control systems on the timeliness of financial reports. The sample used was 48 respondents. The data analysis method used is multiple linear regression analysis, and hypothesis verification using the t test, F test, and coefficient of determination analysis. The results of multiple linear regression analysis obtained Y = 2.620 + 0.475X1 + 0.791X2 + 0.418X3. The result of the coefficient of determination (Adjusted R Square) is 0.664 or as a percentage it is 61.7%. This shows that the variable utilization of information technology, human resource capacity and internal control systems on the timeliness of financial reports is 61.7%, while the remaining 28.3% is influenced by other variables not examined in this research. The t test results were obtained by utilizing information technology, human resource capacity, and internal control systems on the timeliness of financial reports. The F test results obtained by the use of information technology, human resource capacity and internal control systems have a significant effect on the timeliness of financial reports.